Kompleksitas Masyarakat Indonesia Kontemporer - Maulana, Rizal (Universitas Islam Indonesia, 2019)
The picture of the Indonesian in “The New Order” with a variety of needs and conflicts was a problem that later led to the Reformation Era marked by the “fall” of Suharto from his position as President of the Indonesian Republic after ruling for 32 years. The communities appear to have diverse roles. The various forms of behaviour reflected the conditions and circumstances of each, either as an individual or group. Pillage, rape, accusation, blasphemy, on one hand and the establishment of new parties, demonstrations and congregational prayers on the other colour Indonesian society today. A land of a thousand islands with a song of “Nyiur Melambai” (Waving Palm) which symbolizes comfort and peace as it is now has weakened in sorrow, lamenting the fate of the nation that looks ‘messy’ by the variety of concerns and needs of some people. A condition in the nation’s life perceived as a slump becomes difficult to evolve for a better future of a country. The condition appearing in society no longer characterizes the role model of the laws and concern of lives that gave peace and happiness to humanity.Keywords:Conflict, Reformation, Discrepancy, Role Model, Peace, Happiness